Data communication system using portable two-way radio / Mohd Shukri Ahmad - Ahmad, Mohd Shukri (1998)
Traditionally, the Personal Computer (PC) is connected via Local Area Network (LAN) using the wireless data services and systems, cost effectiveness and flexibility can be achieved as the PC can be moved around without additional hard wire required for the LAN. This project thesis presents the use of radio frequency portable two-way-radio GP300 as a medium for wireless data communication. The objective of this project is to study bit error rate (BER), modulation types and signal speeds for wireless data communication (WDC) using portable two-way radio (walkie-talkie), voice band modem and PC. It will be a lowcost (without line charge, access fee), low-speed (less than few kilobits per second) communication system with a range of a few meter to hundred meter or in building environment. This WDC system has applications such as remote weather station, telemetry system, and portable data terminal in building.